An identity for Stirling numbers of the second kind - Tuladhar, B. M.; López-Bonilla, J.; Salas-Torres, O. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
We obtain an identity satisfied by the Stirling numbers of the second kind. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 1, 2017, Page: 95-97